Analyzing the influence of employee values on knowledge management in sport organizations. Issue 3 (28th June 2019) - Delshab, Vahid; Winand, Mathieu; Sadeghi Boroujerdi, Saeed; Pyun, Do Young; Mahmoudian, Abed
Abstract : Purpose: The purpose of this study is to investigate the relationship between employee values and knowledge management (KM) in sport organizations. Design/methodology/approach: Data ( N = 234) were collected online through a structured questionnaire from employees of 33 sport organizations in Iran. To test the hypotheses, Pearson correlation test and a regression analysis was conducted. Findings: The results from the study revealed that there were significant relationships between employee values and KM. Both instrumental and terminal values significantly influenced KM. Research limitations/implications: One limitation of this study is related to the generalizability of the results. Therefore, the current study is required to be replicated with other sport organizations in various sectors (public or private) to improve external validity of the results. Practical implications: Based on this study, employees of sport organizations in developing countries tend to store knowledge more than sharing and applying it. The findings can be used by human resources and KM practitioners who are interested in developing organizational knowledge through employees' values. Originality/value: Through this study, the positive roles of employee instrumental and terminal values, as the key drivers in determining intangible assets in organizations, were found.